1983
DOI: 10.1111/j.1651-2227.1983.tb09659.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Training on Exercise‐induced Bronchoconstriction

Abstract: A 6-week period of physical training of 28 asthmatic children reduced the exercise-induced percentage fall in peak expiratory flow (from baseline) from 44 +/- 4% (mean +/- SE) to 30 +/- 4%. Resting pulmonary function was unchanged. Resting and maximum heart rate (submaximal treadmill running) and postexercise plasma lactate were all lowered by training. The individual values for exercise-induced bronchoconstriction and postexercise plasma lactate correlated positively before and after training. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
6

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 14 publications
2
17
0
6
Order By: Relevance
“…Interestingly, these observations parallel the findings of previous clinical studies, which documented improvements in exercise-induced bronchoconstriction after physical training (36)(37)(38)(39)(40). Specifically, reports from Emtner and coworkers and from Henriksen and Nielsen each demonstrated that adults with mild-moderate asthma who participated in an aerobic exercise training program exhibited decreased exercise-induced bronchospasm (36,37).…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, these observations parallel the findings of previous clinical studies, which documented improvements in exercise-induced bronchoconstriction after physical training (36)(37)(38)(39)(40). Specifically, reports from Emtner and coworkers and from Henriksen and Nielsen each demonstrated that adults with mild-moderate asthma who participated in an aerobic exercise training program exhibited decreased exercise-induced bronchospasm (36,37).…”
Section: Discussionsupporting
confidence: 77%
“…Additional studies have reported similar findings with regard to exercise-mediated improvement in the ventilatory capacity of asthmatic patients (9,11). It is interesting to note that several of these studies observed improvements in exercise-induced bronchoconstriction following physical training (7,9,10). In light of these observations, there may exist an inverse dose response for the efficacy of exercise in the treatment of asthma.…”
Section: Discussionmentioning
confidence: 65%
“…Given that exercise modulates immune responses in healthy individuals (4 -6), consideration of the clinical ramifications of exercise in the modification of a disease for which the immune system has a role is of vital importance. Several clinical studies suggest that aerobic exercise training improves the overall physical fitness and health of asthmatics through increasing ventilatory capacity and lessening of asthma-related symptoms (7)(8)(9)(10)(11). American Thoracic Society guidelines for pulmonary rehabilitation programs, in accordance with these clinical studies, recommend the implementation of low to moderate intensity aerobic exercise training for those with chronic respiratory disease, including asthma (12).…”
mentioning
confidence: 99%
“…Improved physical fitness in asthmatic subjects has, in some studies, contributed to a reduction in the occurrence of respiratory symptoms and medicine consumption [13,14,25] but not in all studies [15]. The ability of physical training to reduce the fall in FEV1 after exercise is also conflicting [15,26]. This may be due to the weak correlation between physical fitness and airway reactivity.…”
Section: Discussionmentioning
confidence: 97%